PENGARUH METODE PROBLEM BASED LEARNING TERHADAP HASIL PEMBELAJARAN TEMATIK PADA SISWA KELAS V SDN LENGKONG WETAN 01 - Frisca Febiyanti; Yeni Nuraeni; Septy Nurfadhillah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to determine the effect of using the Problem Based Learning (PBL) Learning model on Learning outcomes in the theme "National Events during the Colonial Period". This research is an experimental research, a Quasi experimental research type. The population of this study were all 5th grade students at SDN Lengkong Wetan 01, the sampling technique used was saturated sampling with a sample of 30 students from the experimental class and 30 students from the control class. Data collection techniques in this study were observation, Learning outcomes tests in the form of multiple choice questions (pretest and post-tests) and documentation. Data collection uses an instrument in the form of multiple choice tests that have been tested for validity and reliability. Based on the results of posttest calculations using the t-test at a significance level of α = 0.05%, tcount (3.74) > ttable (2.0017) is obtained. So it can be concluded that the Problem Based Learning (PBL) method has an effect on Learning Outcomes Theme 7 national events during the colonial period in Class V students at SDN Lengkong Wetan 01.